Análisis jurídico de la aplicación de las medidas de protección, otorgadas en casos de violencia contra la mujer en el cantón Ibarra, durante el periodo 2022-2023 - Revelo Sierra, Jhon Jairo (2024)
The 2008 Constitution of Ecuador establishes solid protection of the rights of priority groups, recognizing diversity and promoting equality. First of all, it gives special attention to older adults, girls, boys and adolescents, pregnant women, etc. It establishes that these populations must receive priority and specialized attention in the public and private spheres. Additionally, the 2008 Ecuadorian Constitution highlights the importance of protecting people in situations of double vulnerability, such as those affected by domestic violence, child abuse or natural disasters. In accordance with the law to eradicate violence against women, the Constitution highlights the need to prevent and eliminate violence against women, transforming multicultural models that promulgate inequality between men and women. This investigative work was addressed in a comprehensive manner and focuses on the legal framework that supports protection measures for women, ensuring a deep understanding of the current provisions and their practical application in situations of gender violence, and a critical evaluation is also carried out. Of the effectiveness of the measures implemented, highlighting both the achievements achieved and the challenges identified. Likewise, it provides relevant statistical data, from a quantitative view that illustrates the magnitude of violence against women in the Ibarra canton. Specific strategic recommendations are also made to strengthen the protection system, offering practical ways to improve effectiveness and promptness. In the legal response to cases of violence against women. This research is supported by a rigorous methodology, which not only informs legal professionals and legislators, but also stands out as an essential tool for the formulation of public policies that seek to eradicate gender violence in all its forms.